2016
DOI: 10.20944/preprints201609.0019.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ethnic Differences in the Food Intake Patterns and Its Association Factors of Adolescents in Malaysia

Abstract: Objective: The aim of the study was to identify dietary patterns and its association with socio-economic, dietary and lifestyle practices among adolescents in Malaysia. Methods: A validated food frequency questionnaire was used to assess dietary patterns. Results: Multivariate analyses show that age and physical activity (PA) levels were emerged as positive determinants of healthy-based food pattern in Malay (All, p<0.001), whereas higher consumption of eating-out from home (EatOut) and fast food (All, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Non-Chinese adolescents were more likely to consume fast food than Chinese adolescents. The findings from this study are also in line with a previous Malaysian study that found Chinese adolescents consumed healthier food than Malay adolescents [ 21 ]. Two possible reasons for the ethnic differences in fast-food consumption were identified.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Non-Chinese adolescents were more likely to consume fast food than Chinese adolescents. The findings from this study are also in line with a previous Malaysian study that found Chinese adolescents consumed healthier food than Malay adolescents [ 21 ]. Two possible reasons for the ethnic differences in fast-food consumption were identified.…”
Section: Discussionsupporting
confidence: 92%
“…The finding of this study contradicts with other studies [ 19 , 20 ]. A previous study found that adolescent girls were more likely to visit fast-food outlets in special days to meet with friends or family than boys especially in city centres [ 21 ]. Another previous study disclosed that the main reasons of adolescent girls consuming fast food were enjoying the taste of fast food and favouring the convenience of the fast-food restaurants [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation